Diaphragm coating slurry composition and preparation method thereof, diaphragm and preparation method thereof, and lithium battery

By using coating compositions such as inorganic ceramic powder and high-temperature resistant polymer nanofibers in lithium battery separators, the problem of insufficient heat resistance performance of traditional separators at high temperatures is solved, and the high-temperature resistance performance of lithium batteries is improved and Improved cycle performance.

CN119208916APending Publication Date: 2024-12-27HUZHOU NANMU-NANO SCI & TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411298334.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The heat resistance of traditional lithium battery separators under high temperature conditions is insufficient, which affects the battery's rate performance, charge and discharge function and cycle life.

Method used

It is prepared by uniform mixing and stirring using a diaphragm coating slurry composition, including inorganic ceramic powder, high temperature resistant polymer nanofibers, ionic dispersants, polymer dispersants, wetting agents, binders and solvents. A diaphragm coating with good high temperature resistance is formed, applied on the base film and dried to form a diaphragm with improved high temperature resistance is formed.

Benefits of technology

It significantly improves the high temperature resistance of the diaphragm, enhances the circulation performance and ionic conductivity of the lithium battery, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005046806590000021
    Figure BDA0005046806590000021
  • Figure BDA0005046806590000051
    Figure BDA0005046806590000051
  • Figure BDA0005046806590000101
    Figure BDA0005046806590000101
Patent Text Reader

Abstract

The invention relates to a diaphragm coating slurry composition and a preparation method thereof, a diaphragm and a preparation method thereof, and a lithium battery. The diaphragm coating slurry composition is prepared from the following components in parts by mass: 30 to 40 parts of inorganic ceramic powder, 10 to 20 parts of high-temperature-resistant polymer nanofiber, 0.2 to 0.6 part of an ionic dispersing agent, 0.1 to 0.3 part of a polymer dispersing agent, 0.6 to 1.2 parts of a wetting agent, 3 to 8 parts of a binding agent and 50 to 60 parts of a solvent, wherein the thermal decomposition temperature of the high-temperature-resistant polymer nanofiber is not lower than 200 DEG C. The combination of the components and the mass fraction range of the components are determined through a large number of tests, and the combination and the mass fraction range enable a diaphragm coating formed by the diaphragm coating slurry composition to have good high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium batteries, and in particular to a diaphragm coating slurry composition and a preparation method thereof, a diaphragm and a preparation method thereof, and a lithium battery. Background Art

[0002] In recent years, due to resource and environmental issues, lithium batteries have become the focus of development in the field of new energy. As one of the core components of lithium batteries, lithium battery separators can prevent short circuits between the positive and negative electrodes of the battery on the one hand, and transmit free ions on the other hand. The performance of the separator will greatly affect the rate performance, charge and discharge function, cycle life, etc. of the battery, so the separator is required to have good insulation performance, mechanical strength, chemical stability, and thermal stability.

[0003] In traditional technology, ceramic coating modification of the diaphragm can simply and effectively improve the high temperature resistance of the diaphragm, but the improvement effect is not very obvious. Summary of the invention

[0004] Based on this, it is necessary to provide a diaphragm coating slurry composition and a preparation method thereof, a diaphragm and a preparation method thereof, and a lithium battery in order to improve the high temperature resistance of the diaphragm.

[0005] A diaphragm coating slurry composition, which comprises the following components in parts by mass:

[0006] 30 to 40 parts of inorganic ceramic powder;

[0007] 10 to 20 parts of high temperature resistant polymer nanofibers;

[0008] 0.2 to 0.6 parts of ionic dispersant;

[0009]

[0010] Wherein, the thermal decomposition temperature of the high temperature resistant polymer nanofiber is not less than 200°C.

[0011] In the above-mentioned diaphragm coating slurry composition, adding high temperature resistant polymer nanofibers to the inorganic ceramic powder can improve the high temperature resistance of the diaphragm, the ionic dispersant helps to disperse the inorganic ceramic powder, the polymer dispersant helps to disperse the high temperature resistant polymer nanofibers, the wetting agent helps to wet the components, the binder helps to bond the components, and the solvent is used to dissolve the components. The combination of these components and the above-mentioned mass fraction range of each component are determined through a large number of tests, and the above-mentioned combination and mass fraction range make the diaphragm coating formed by the diaphragm coating slurry composition of the present invention have good high temperature resistance.

[0012] In a feasible implementation, the inorganic ceramic powder is selected from at least one of silicon dioxide, aluminum oxide, boehmite, cerium dioxide, titanium dioxide, magnesium oxide and zirconium dioxide; the D50 particle size of the inorganic ceramic powder is 0.6 μm to 0.9 μm, and the D100 particle size of the inorganic ceramic powder is 2 μm to 3 μm; and / or

[0013] The high temperature resistant polymer nanofiber is selected from at least one of polyimide nanofiber, polyaramid nanofiber, polybenzoxazole nanofiber, polysilane nanofiber and carborane nanofiber; the diameter of the high temperature resistant polymer nanofiber is 10nm-20nm, and the length of the high temperature resistant polymer nanofiber is 100nm-200nm.

[0014] In a feasible implementation, the ionic dispersant is selected from at least one of sodium hexametaphosphate, sodium tripolyphosphate, sodium citrate, sodium dodecylbenzene sulfonate and ammonium polyacrylate; and / or

[0015] The polymer dispersant is at least one selected from the group consisting of fatty acid ethylene oxide adducts, polyethylene glycol type polyols and polyethyleneimine derivatives; and / or

[0016] The wetting agent is selected from at least one of methyl acrylate, OP-10, ethanol, propylene glycol, glycerol, dimethyl sulfoxide, alkyl sulfate, sulfonate and fatty acid; and / or

[0017] The binder is selected from at least one of sodium carboxymethyl cellulose, polyacrylate, styrene-butadiene rubber, polyurethane and polyacrylonitrile; and / or

[0018] The solvent is selected from at least one of deionized water, alcohol solvents and N-methylpyrrolidone.

[0019] A method for preparing any of the above-mentioned diaphragm coating slurry compositions comprises the following steps:

[0020] Inorganic ceramic powder, high temperature resistant polymer nanofibers, ionic dispersant, polymer dispersant, wetting agent, binder and solvent are uniformly mixed according to mass proportions to obtain a diaphragm coating slurry composition.

[0021] The preparation method of the diaphragm coating slurry composition is simple in process, and the prepared diaphragm coating slurry composition has good high temperature resistance.

[0022] In a feasible implementation, the operation of uniformly mixing the inorganic ceramic powder, the high temperature resistant polymer nanofiber, the ionic dispersant, the polymer dispersant, the wetting agent, the binder and the solvent is as follows:

[0023] The inorganic ceramic powder, ionic dispersant, wetting agent and solvent are stirred in a disperser, and the stirring time is maintained for 30min to 40min, and the stirring speed is 2000r / min to 4000r / min; then the polymer dispersant and high temperature resistant polymer nanofiber are added in sequence and the stirring is continued, and the stirring time is maintained for 40min to 60min, and the stirring speed is 3000r / min to 4000r / min; then the binder is added and the stirring is continued, and the stirring time is maintained for 20min to 30min, and the stirring speed is 500r / min to 800r / min.

[0024] A diaphragm comprises a base film, at least one surface of the base film is covered with a coating, and the coating is prepared from any of the above-mentioned diaphragm coating slurry compositions.

[0025] Experiments have shown that the diaphragm of the technical solution of the present invention has good high temperature resistance.

[0026] In a feasible implementation, the base film is a polyethylene film or a polypropylene film; the thickness of the base film is 9 μm to 12 μm; and the thickness of the coating is 1 μm to 4 μm.

[0027] A method for preparing a diaphragm comprises the following steps:

[0028] The diaphragm is coated on at least one side of the base film with any of the above-mentioned diaphragm coating slurry compositions, and then dried to obtain the diaphragm.

[0029] Experiments have shown that the diaphragm obtained by the diaphragm preparation method of the technical solution of the present invention has good high temperature resistance.

[0030] In a feasible implementation, the coating speed is 50 m / min to 70 m / min; the drying temperature is 80° C. to 100° C., and the drying time is 30 min to 90 min.

[0031] A lithium battery comprises the above-mentioned separator.

[0032] In the lithium battery of the technical solution of the present invention, the diaphragm has good high temperature resistance. DETAILED DESCRIPTION

[0033] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0034] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0035] The diaphragm coating slurry composition of one embodiment includes the following components in parts by mass:

[0036] 30 to 40 parts of inorganic ceramic powder;

[0037] 10 to 20 parts of high temperature resistant polymer nanofibers;

[0038]

[0039] Wherein, the thermal decomposition temperature of the high temperature resistant polymer nanofiber is not less than 200°C.

[0040] Among them, the thermal decomposition temperature (Td) refers to the degradation of the molecular chain when the polymer is heated to a certain temperature. As the temperature further increases, the degradation will accelerate. When the temperature rises to the point where the weight loss of the polymer sample suddenly accelerates, this temperature is the thermal decomposition temperature.

[0041] In the above-mentioned diaphragm coating slurry composition, adding high temperature resistant polymer nanofibers to the inorganic ceramic powder can improve the high temperature resistance of the diaphragm, the ionic dispersant helps to disperse the inorganic ceramic powder, the polymer dispersant helps to disperse the high temperature resistant polymer nanofibers, the wetting agent helps to wet the components, the binder helps to bond the components, and the solvent is used to dissolve the components. The combination of these components and the above-mentioned mass fraction range of each component are determined through a large number of tests, and the above-mentioned combination and mass fraction range make the diaphragm coating formed by the diaphragm coating slurry composition of the present invention have good high temperature resistance.

[0042] Based on the above-mentioned embodiment, the inorganic ceramic powder is selected from at least one of silicon dioxide (SiO2), aluminum oxide (Al2O3), boehmite (AlO(OH)n), cerium dioxide (CeO2), titanium dioxide (TiO2), magnesium oxide (MgO) and zirconium dioxide (ZrO2); the D50 particle size of the inorganic ceramic powder is 0.6μm~0.9μm, and the D100 particle size of the inorganic ceramic powder is 2μm~3μm.

[0043] On the basis of the above-mentioned implementation mode, the high temperature resistant polymer nanofiber is selected from at least one of polyimide nanofiber, polyaramid nanofiber, polybenzoxazole nanofiber, polysilane nanofiber and carborane nanofiber; the diameter of the high temperature resistant polymer nanofiber is 10nm-20nm, and the length of the high temperature resistant polymer nanofiber is 100nm-200nm. Among them, polyimide is an engineering plastic with excellent heat resistance, and its initial thermal decomposition temperature can reach above 500℃, and its low temperature resistance is also excellent, and it can withstand low temperatures of -260℃; the use temperature range of polyaramid is -196℃-204℃, and it also has excellent high and low temperature resistance.

[0044] It should be noted that in the diaphragm coating slurry composition of the present invention, the high temperature resistant polymer nanofibers may be polyimide nanofibers or polyaramid nanofibers, or may be a mixture of polyimide nanofibers and polyaramid nanofibers.

[0045] On the basis of the above-mentioned embodiment, the ionic dispersant is selected from at least one of sodium hexametaphosphate, sodium tripolyphosphate, sodium citrate, sodium dodecylbenzene sulfonate and ammonium polyacrylate.

[0046] Based on the above embodiments, the polymer dispersant (also called super dispersant) is selected from at least one of fatty acid ethylene oxide adducts, polyethylene glycol type polyols and polyethyleneimine derivatives. Further, the polymer dispersant can be, for example, AD8085 dispersant.

[0047] Based on the above embodiment, the wetting agent is selected from at least one of methyl acrylate, OP-10 (component is dodecylphenol polyoxyethylene ether), ethanol, propylene glycol, glycerol, dimethyl sulfoxide, alkyl sulfate, sulfonate and fatty acid.

[0048] Based on the above-mentioned embodiment, the binder is selected from at least one of sodium carboxymethyl cellulose, polyacrylate, styrene-butadiene rubber, polyurethane and polyacrylonitrile.

[0049] Based on the above implementation, the solvent is selected from at least one of deionized water, alcohol solvent and N-methylpyrrolidone.

[0050] Experiments have shown that the above combination and mass fraction range enable the diaphragm coating formed by the diaphragm coating slurry composition of the present invention to have good high temperature resistance.

[0051] A method for preparing a diaphragm coating slurry composition according to one embodiment comprises the following steps:

[0052] Inorganic ceramic powder, high temperature resistant polymer nanofibers, ionic dispersant, polymer dispersant, wetting agent, binder and solvent are uniformly mixed according to mass proportions to obtain a diaphragm coating slurry composition.

[0053] On the basis of the above-mentioned embodiment, the operation of uniformly mixing the inorganic ceramic powder, the high temperature resistant polymer nanofiber, the ionic dispersant, the polymer dispersant, the wetting agent, the binder and the solvent is as follows:

[0054] The inorganic ceramic powder, ionic dispersant, wetting agent and solvent are stirred in a disperser, and the stirring time is maintained for 30min to 40min, and the stirring speed is 2000r / min to 4000r / min; then the polymer dispersant and high temperature resistant polymer nanofiber are added in sequence and the stirring is continued, and the stirring time is maintained for 40min to 60min, and the stirring speed is 3000r / min to 4000r / min; then the binder is added and the stirring is continued, and the stirring time is maintained for 20min to 30min, and the stirring speed is 500r / min to 800r / min.

[0055] The preparation method of the diaphragm coating slurry composition is simple in process, and the prepared diaphragm coating slurry composition has good high temperature resistance.

[0056] A diaphragm according to one embodiment is characterized in that it comprises a base film, at least one surface of the base film is covered with a coating, and the coating is prepared from any of the above-mentioned diaphragm coating slurry compositions.

[0057] On the basis of the above-mentioned embodiment, the base film is a polyethylene film or a polypropylene film; the thickness of the base film is 9 μm to 12 μm; the thickness of the coating is 1 μm to 4 μm. Among them, the polyethylene film and the polypropylene film are both non-polar polymer films, and have poor compatibility with polar electrolytes. By covering with the above-mentioned inorganic ceramic coating, the lyophilicity of the base film and the electrolyte can be increased, and the liquid holding rate of the diaphragm can be greatly increased.

[0058] Experiments have shown that the diaphragm of the technical solution of the present invention has good high temperature resistance.

[0059] A method for preparing a diaphragm according to one embodiment comprises the following steps:

[0060] The diaphragm is coated on at least one side of the base film with any of the above-mentioned diaphragm coating slurry compositions, and then dried to obtain the diaphragm.

[0061] Based on the above embodiment, the coating speed is 50m / min to 70m / min, the drying temperature is 80°C to 100°C, and the drying time is 30min to 90min. The drying operation can be performed in a vacuum oven.

[0062] Experiments have shown that the diaphragm obtained by the diaphragm preparation method of the technical solution of the present invention has good high temperature resistance.

[0063] A lithium battery according to an embodiment of the present invention is characterized by comprising any of the above-mentioned separators, wherein the lithium battery can be a lithium metal battery or a lithium ion battery.

[0064] In the lithium battery of the technical solution of the present invention, the diaphragm has good high temperature resistance.

[0065] With reference to the above implementation contents, in order to make the technical solution of the present application more specific, clear and easy to understand, the technical solution of the present application is now exemplified. However, it should be noted that the contents to be protected by the present application are not limited to the following embodiments 1 to 3.

[0066] Example 1

[0067] 35g of special alumina (D50 particle size is 0.6μm, D100 particle size is 4μm), 0.2g of sodium hexametaphosphate, 0.6g of OP-10 and 50g of deionized water are added to a disperser and stirred to mix evenly, and the stirring time is maintained for 60min and the stirring speed is 3000r / min; then 0.2g of analytical grade polyethylene glycol and 10g of polyimide nanofibers (diameter is 10nm, length is 100nm, manufacturer is Jiangsu Xiannuo New Material Technology Co., Ltd.) are added and continued stirring is maintained for 50min and the stirring speed is 3000r / min; then 5g of polyacrylonitrile is added and continued stirring is maintained for 20min and the stirring speed is 500r / min to obtain the diaphragm coating slurry composition of Example 1.

[0068] The above-mentioned diaphragm coating slurry composition was coated on one side surface of a 9 μm thick PE base film, wherein the coating speed was 50 m / min, and the thickness of the coating obtained after coating was 3.5 μm, and then dried to obtain the diaphragm of Example 1, wherein the drying temperature was 80° C. and the drying time was 1 h.

[0069] Take the membrane trial battery prepared in Example 1, the battery model is ternary 18650, wherein: ternary material NCM523 is used as the anode, graphite is used as the cathode, the solute in the electrolyte is lithium hexafluorophosphate, and the solvent is ethylene carbonate, so as to obtain the lithium ion battery of Example 1.

[0070] Example 2

[0071] 30g of special alumina (D50 particle size is 0.5μm, D100 particle size is 3μm), 0.2g of ammonium polyacrylate, 0.9g of OP-10 and 54g of deionized water are added to a disperser and stirred to mix evenly, and the stirring time is maintained for 60min and the stirring speed is 3000r / min; then 0.2g of polyethyleneimine and 10g of polyimide nanofibers (diameter is 10nm, length is 100nm) are added and continued stirring, and the stirring time is maintained for 30min and the stirring speed is 3000r / min; then 6g of polyacrylonitrile is added and continued stirring, and the stirring time is maintained for 20min and the stirring speed is 500r / min to obtain the diaphragm coating slurry composition of Example 2.

[0072] The above-mentioned diaphragm coating slurry composition was coated on one side surface of a 9 μm thick PE base film, wherein the coating speed was 40 m / min, and the thickness of the coating obtained after coating was 3 μm, and then dried to obtain the diaphragm of Example 2, wherein the drying temperature was 80° C. and the drying time was 1 h.

[0073] Take the membrane trial battery prepared in Example 2, the battery model is ternary 18650, wherein: ternary material NCM523 is used as the anode, graphite is used as the cathode, the solute in the electrolyte is lithium hexafluorophosphate, and the solvent is ethylene carbonate, so as to obtain the lithium ion battery of Example 2.

[0074] Example 3

[0075] 40g of silica (D50 particle size is 0.5μm, D100 particle size is 3μm), 0.3g of sodium citrate, 0.7g of OP-10 and 44g of deionized water are added to a disperser and stirred to mix evenly, and the stirring time is maintained for 60min and the stirring speed is 3000r / min; then 0.2g of AD8085 dispersant (manufacturer is Guangdong Rongdong) and 12g of polyaramid fiber (diameter is 10nm, length is 100nm) are added and continued stirring, and the stirring time is maintained for 40min and the stirring speed is 3000r / min; then 4g of polyacrylonitrile is added and continued stirring, and the stirring time is maintained for 20min and the stirring speed is 500r / min to obtain the diaphragm coating slurry composition of Example 3.

[0076] The above-mentioned diaphragm coating slurry composition was coated on one side surface of a PE base film with a thickness of 9 μm, wherein the coating speed was 40 m / min, and the thickness of the coating obtained after coating was 3 μm, and then dried to obtain the diaphragm of Example 3, wherein the drying temperature was 80°C and the drying time was 1 h.

[0077] Take the membrane test battery prepared in Example 3, the battery model is ternary 18650, wherein: ternary material NCM523 is used as the anode, graphite is used as the cathode, the solute in the electrolyte is lithium hexafluorophosphate, and the solvent is ethylene carbonate. The lithium ion battery of Example 3 is obtained.

[0078] Performance Test:

[0079] (1) The appearance, thickness, air permeability, heat shrinkage at different temperatures, liquid absorption rate and peel strength of the separators of Examples 1 to 3 were tested. The test method is as follows. The test results are shown in Table 1.

[0080] Appearance: Observe with naked eyes;

[0081] Thickness: measured by Mahr thickness gauge;

[0082] Air permeability: measured by air permeability meter;

[0083] Thermal shrinkage: Place the sample in an oven at 130 degrees Celsius for one hour and clamp it with a glass plate;

[0084] Liquid absorption rate: Based on QB / T2303.11-2008 "Battery pulp layer paper Part 11: Determination of liquid absorption rate", according to the formula η=〔(M1-M0) / M0〕×100%, where M0 and M1 are the masses of the diaphragm before and after immersion in the electrolyte respectively;

[0085] Peel strength: Sample preparation: Cut a separator with a size of 1.5 cm×20 cm and perform a peel test using a peel tester at an angle of 180° and a speed of 300 mm / min.

[0086] Table 1 Performance test results of the diaphragms of Examples 1 to 3

[0087]

[0088] It can be seen from Table 1 that the coating layers of the diaphragms of Examples 1 to 3 of the present invention are uniform, smooth, without color difference and defects such as missing coating that can be seen by the naked eye, and the thermal shrinkage at 150°C / 1h is only 1% to 2% in MD and 1% to 2% in TD, which is significantly better than the 10% to 20% of products of the same thickness in the prior art, indicating that the diaphragms of Examples 1 to 3 have stronger heat resistance; the diaphragms of Examples 1 to 3 have lower air permeability, providing more channels for ions to pass through, thereby increasing the wettability to the electrolyte.

[0089] (2) The battery cycle performance of the lithium ion batteries of Examples 1 to 3 was tested at room temperature. The test results are shown in Table 2. The test method is: discharge with a current of 1C to the termination voltage, leave for 30 minutes, charge in a standard manner, leave for 30 minutes or the shelf time specified by the enterprise, discharge with a current of 1C to the termination condition, record the discharge capacity and energy, repeat the charge and discharge until the battery capacity decays to the specified value, and record the number of charge and discharge cycles.

[0090] The charge and discharge performance of the lithium ion batteries of Examples 1 to 3 were tested. The test results are shown in Table 2. The test method is: after charging in a standard manner, storing at a specified temperature for a specified time (28 days at room temperature or 7 days at 55°C), leaving at room temperature for 5 hours, discharging at a current of 1C until any single cell reaches the discharge termination voltage, calculating the charge retention capacity, and then charging in a standard manner, discharging at a current of 1C at room temperature until any single cell reaches the termination voltage, and calculating the recovery capacity.

[0091] Table 2 Performance test results of lithium ion batteries of Examples 1 to 3

[0092]

[0093] It can be seen from Table 2 that the separators of Examples 1 to 3 of the present invention can effectively improve the cycle performance of lithium-ion batteries and enhance the ionic conductivity of lithium batteries.

[0094] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0095] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A membrane coating slurry composition, characterized in that: The diaphragm coating slurry composition comprises the following components in parts by mass: Wherein, the thermal decomposition temperature of the high temperature resistant polymer nanofiber is not less than 200°C.

2. The diaphragm coating slurry composition according to claim 1, characterized in that: The inorganic ceramic powder is selected from at least one of silicon dioxide, aluminum oxide, boehmite, cerium dioxide, titanium dioxide, magnesium oxide and zirconium dioxide; the D50 particle size of the inorganic ceramic powder is 0.6 μm to 0.9 μm, and the D100 particle size of the inorganic ceramic powder is 2 μm to 3 μm; and / or The high temperature resistant polymer nanofiber is selected from at least one of polyimide nanofiber, polyaramid nanofiber, polybenzoxazole nanofiber, polysilane nanofiber and carborane nanofiber; the diameter of the high temperature resistant polymer nanofiber is 10nm-20nm, and the length of the high temperature resistant polymer nanofiber is 100nm-200nm.

3. The diaphragm coating slurry composition according to claim 1, characterized in that: The ionic dispersant is selected from at least one of sodium hexametaphosphate, sodium tripolyphosphate, sodium citrate, sodium dodecylbenzene sulfonate and ammonium polyacrylate; and / or The polymer dispersant is at least one selected from the group consisting of fatty acid ethylene oxide adducts, polyethylene glycol type polyols and polyethyleneimine derivatives; and / or The wetting agent is selected from at least one of methyl acrylate, OP-10, ethanol, propylene glycol, glycerol, dimethyl sulfoxide, alkyl sulfate, sulfonate and fatty acid; and / or The binder is selected from at least one of sodium carboxymethyl cellulose, polyacrylate, styrene-butadiene rubber, polyurethane and polyacrylonitrile; and / or The solvent is selected from at least one of deionized water, alcohol solvents and N-methylpyrrolidone.

4. A method for preparing the diaphragm coating slurry composition according to any one of claims 1 to 3, characterized in that: The steps include: Inorganic ceramic powder, high temperature resistant polymer nanofibers, ionic dispersant, polymer dispersant, wetting agent, binder and solvent are uniformly mixed according to mass proportions to obtain a diaphragm coating slurry composition.

5. The method for preparing the diaphragm coating slurry composition according to claim 4, characterized in that: The operation of uniformly mixing the inorganic ceramic powder, the high temperature resistant polymer nanofiber, the ionic dispersant, the polymer dispersant, the wetting agent, the binder and the solvent is as follows: The inorganic ceramic powder, ionic dispersant, wetting agent and solvent are stirred in a disperser, and the stirring time is maintained for 30min to 40min, and the stirring speed is 2000r / min to 4000r / min; then the polymer dispersant and high temperature resistant polymer nanofiber are added in sequence and the stirring is continued, and the stirring time is maintained for 40min to 60min, and the stirring speed is 3000r / min to 4000r / min; then the binder is added and the stirring is continued, and the stirring time is maintained for 20min to 30min, and the stirring speed is 500r / min to 800r / min.

6. A diaphragm, characterized in that: The invention comprises a base film, at least one side of which is covered with a coating, wherein the coating is prepared from the diaphragm coating slurry composition according to any one of claims 1 to 3.

7. The diaphragm according to claim 6, characterized in that The base film is a polyethylene film or a polypropylene film; the thickness of the base film is 9 μm to 12 μm; the thickness of the coating is 1 μm to 4 μm.

8. A method for preparing a diaphragm, characterized in that: The steps include: The diaphragm coating slurry composition according to any one of claims 1 to 3 is applied to at least one surface of a base film, and then dried to obtain a diaphragm.

9. The method for preparing a diaphragm according to claim 8, characterized in that: The coating speed is 50m / min to 70m / min; the drying temperature is 80℃ to 100℃, and the drying time is 30min to 90min.

10. A lithium battery, characterized in that: Comprising the diaphragm according to claim 6 or 7.

Citation Information

Cited By

  • High-heat-resistance coating slurry as well as preparation method and application thereof

    CN121271305A